2017
DOI: 10.1111/hsc.12481
|View full text |Cite
|
Sign up to set email alerts
|

Attractiveness of working in home care: An online focus group study among nurses

Abstract: Many western countries are experiencing a substantial shortage of home-care nurses due to the increasing numbers of care-dependent people living at home. In-depth knowledge is needed about what home-care nurses find attractive about their work in order to make recommendations for the recruitment and retention of home-care nursing staff. The aims of this explorative, qualitative study were to gain in-depth knowledge about which aspects home-care nurses find attractive about their work and to explore whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 19 publications
2
54
0
Order By: Relevance
“…The results show that most home‐care nurses regard these aspects as attractive. A focus group study by De Groot, Maurits, and Francke () also showed that home‐care nurses feel attracted to the fact that they can be a link between the patient and other professionals, and be responsible for the co‐ordination of care. Reasoning from the study findings, being able to deliver and organise people‐centred, integrated home care may increase home‐care nurses’ job satisfaction and contribute to the retention of nurses in home care.…”
Section: Discussionmentioning
confidence: 99%
“…The results show that most home‐care nurses regard these aspects as attractive. A focus group study by De Groot, Maurits, and Francke () also showed that home‐care nurses feel attracted to the fact that they can be a link between the patient and other professionals, and be responsible for the co‐ordination of care. Reasoning from the study findings, being able to deliver and organise people‐centred, integrated home care may increase home‐care nurses’ job satisfaction and contribute to the retention of nurses in home care.…”
Section: Discussionmentioning
confidence: 99%
“… 15 In addition, the asynchronous format allows participants the ability to contribute at a convenient place and time, making the research more accessible to participants who may be in different time zones with competing demands on their time. 17 …”
Section: Methods and Analysismentioning
confidence: 99%
“…15 In addition, the asynchronous format allows participants the ability to contribute at a convenient place and time, making the research more accessible to participants who may be in different time zones with competing demands on their time. 17 The focus group questions were discussed with members of the research team, particularly those from LMICs, to ensure these were appropriate (box 1).…”
Section: Data Collectionmentioning
confidence: 99%
“…A survey was developed by a focus group using virtual communication channels. This technique has been used previously in other studies with satisfactory results and was primarily used due to social distancing requirements [18,19]. Medical doctors from different hospitals in the city of Guayaquil, Ecuador, were included.…”
Section: Survey Instrumentmentioning
confidence: 99%